Pre-Match Psychological Readiness and Originality of Team Players in Football - Ibragimov Alisher Karomatovich; Saidmurodova Gavxar Navruzovna (Research Parks Publishing LLC, 2022)
Efforts are being made to increase the level of psychological training of handguns around the world in a number of areas, including the distribution and planning of training loads, competitions and special exercises to improve the psychological skills of hand gunners. Management and their biomechanical analysis, the effect of training loads on psychological preparation, the selection of specific auxiliary exercises and their impact on the biomechanical structure of competition exercises.